PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA CV. PESONA MITRATAMA ELEKTRINDO BEKASI - Ayu Nurul Fatimah; Aden Prawiro Sudarso (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to examine the effect of Organizational Culture and Job Satisfaction on Employee Performance at CV. Pesona Mitratama Elektrindo Bekasi, both partially and simultaneously. The research method used in this study is a quantitative method. The sample consists of 70 employees. Data collection techniques involve both primary and secondary data. The results of the analysis show that: (1) partially, there is a positive influence of Organizational Culture on Employee Performance at CV. Pesona Mitratama Elektrindo Bekasi, as evidenced by the regression equation Y = 13.220 + 0.752X1 and the t-value of 3.143 > t-table 1.996 with a significance value of 0.000 < 0.05. (2) Partially, there is a positive influence of Job Satisfaction on Employee Performance at CV. Pesona Mitratama Elektrindo Bekasi, as evidenced by the regression equation Y = 14.399 + 0.729X2, and the t- value of 7.958 > t-table 1.996 with a significance value of 0.000 < 0.05. (3) Simultaneously, there is a positive influence of Organizational Culture and Job Satisfaction on Employee Performance at CV. Pesona Mitratama Elektrindo Bekasi, as evidenced by the linear regression equation Y = 9.255 + 0.276X1 + 0.575X2, a correlation coefficient of 0.865, a coefficient of determination of 74.9%, and an F-value of 99.778 > F-table 3.13 with a significance level of 0.000 < 0.005.